The anatomy of myth: the art of interpretation from the presocratics to the church fathers - Herren, Michael W. (Oxford University Press, 2017)
The paradigm of the poets -- What makes a work authoritative? -- Physis redefining the gods -- Flirting with atheism -- Attacking poetry -- The beginnings of allegory -- Finding history in myth -- Theos rediscovering God -- The growth of allegory -- Saving the poets without allegory -- From allegory to symbolism -- Greek exegesis and Judaeo-Christian books -- Reflection